PENERBITAN SERTIFIKAT HAK ATAS TANAH MELALUI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KANTOR PERTANAHAN KOTA TANGERANG - Gustiana , Rachmat; Wati Lombu , Jernih Rahmat (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The Complete Systematic Land Registration (PTSL) program is designed to produce detailed maps of land parcels in Tangerang City, covering essential details like location, boundaries, and area. However, the process of issuing land title certificates has often been slow, falling short of public expectations. This situation highlights the need to closely examine how certificates are processed within the PTSL framework. This study centers on the Tangerang City Land Office and uses a qualitative method. Information was collected from key informants considered knowledgeable about the procedures involved. The research found that between 2017 and 2019, the Land Office issued a total of 58,165 land certificates through the PTSL program. Still, several challenges remain especially incomplete ownership documents and the absence of supporting written records. Moving forward, one potential solution is to integrate digital-based land services and expand the use of information technology to streamline and speed up the certification process.